Near‐axis crustal structure and thickness of the Endeavour Segment, Juan de Fuca Ridge - Dax Soule; William S. D. Wilcock; Douglas R. Toomey; Emilie E. E. Hooft; Robert T. Weekly (Geophysical Research Letters)
Abstract A model of crustal thickness and lower crustal velocities is obtained for crustal ages of 0.1–1.2 Ma on the Endeavour Segment of the Juan de Fuca Ridge by inverting travel times of crustal paths and non‐ridge‐crossing wide‐angle Moho reflections obtained from a three‐dimensional tomographic experiment. The crust is thicker by 0.5–1 km beneath a 200 m high plateau that extends across the segment center. This feature is consistent with the influence of the proposed Heckle melt anomaly on the spreading center. The history of ridge propagation on the Cobb overlapping spreading center may also have influenced the formation of the plateau. The sharp boundaries of the plateau and crustal thickness anomaly suggest that melt transport is predominantly upward in the crust. Lower crustal velocities are lower at the ends of the segment, likely due to increased hydrothermal alteration in regions influenced by overlapping spreading centers, and possibly increased magmatic differentiation.